(untitled) (Journal of Student Affairs in Africa, 2021)
Kenya is increasingly turning to the promise of mass higher education to help solve a range of economic and social issues. These efforts have had profound effects on university students, faculty and professionals who provide the vital student support services necessary for academic success. This case study explores the challenges that face Kenyan student services professionals within the context of the country’s history and cultures. Kenya’s student service professionals face four major challenges: the increasing costs of attendance, the resulting impact on student behaviours and actions, lack of training and senior leadership, and regular campus closures.